Phase reconstruction of high-order harmonics by quantum path interference. Issue 7 (January 2020) - Olofsson, A; Ibrakovic, N; Ek, S; Bengtsson, S; Simpson, E R; Mauritsson, J
Synopsis: We present a method to retrieve the phase of XUV light generated through high-order harmonic generation, by observing the intensity dependence of the interference pattern in the far-field. This interference pattern arises from electron trajectories in the generation process. These trajectories spend different time in the continuum and the phase of the generated light will therefore depend differently on the instantaneous intensity of the driving field. By changing the intensity of the driving field the phase of the contributing trajectories can be extracted.